Thanksgiving turkey trouble - Klein, Abby (Klein, Abby., 2008)
Freddy is unhappy about playing the turkey in his first-grade Thanksgiving Day play, especially with Max bullying and teasing him, but his grandfather and principal both give him ideas for making the part fun.